Clinical usefulness of serum angiotensin converting enzyme in silicosis - Blanco-Pérez, J.; Salgado-Barreira, Á.; Blanco-Dorado, S.; González Bello, M.E.; Caldera Díaz, A.C.; Pérez-Gonzalez, A.; Pallarés Sanmartín, A.; Fernández Villar, A.; Gonzalez-Barcala, F.J. (Pulmonology, 2024)
Silicosis is an irreversible and incurable disease. Preventive measures to eliminate exposure are the only effective way to reduce morbidity and mortality. In such situations, having a biomarker for early diagnosis or to predict evolution would be very useful in order to improve control of the disease. The elevation of serum angiotensin-converting enzyme (sACE) in silicosis has been described in previous studies, although its relationship with severity and prognosis is not clear. To determine the levels of sACE in a cohort of patients with exposure to silica dust with and without silicosis, and to assess their impact on the prognosis of the aforementioned patients. Prospective observational study on patients treated in a silicosis clinic from 2009 to 2018. sACE levels and pulmonary function tests were performed. Radiological progression was assessed in patients who had already had 2 X-rays of the thorax and / or two CT scans with at least a 1-year interval, from the time of inclusion in the study. A total of 413 cases of silicosis were confirmed, as well as 73 with exposure to silica dust but without silicosis. The mean sACE level for healthy subjects was 27.5±7.3U/L, for exposed patients without silicosis it was 49.6±24.2U/L, for simple silicosis it was 57.8±31,3U/L and for complicated silicosis it was 74.5±38.6U/L. Patients with a higher sACE generally progressed radiologically during follow-up (73.3±38.0 vs. 60.4±33.7; p<.001) and so the category of silicosis changed (73,9±38.1 vs. 62.5±34.6; p<.021). sACE was elevated in patients with silicosis, and the greater its severity, the higher it was, which is associated with disease progression measured radiologically or as a category change of silicosis.